2021
DOI: 10.21203/rs.3.rs-125188/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Detection of serum KL-6 and SARS-CoV-2 antibody in patients with coronavirus disease 2019 and the diagnostic value in severe disease

Abstract: Background Coronavirus disease 2019 (COVID-19) caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is a significant threat to human health, but its clinical manifestations vary greatly among individuals. Early detection and treatment are important for severely ill patients to improve their prognosis and reduce the risk of death. Methods In the present study, serum markers were detected and analyzed in moderately ill and severely ill patients. Results The results found that there were stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…These articles were re-evaluated based on full-text contents, resulting in exclusion of 8 articles. Finally, 15 studies met the inclusion criteria and were included in our meta-analysis ( Figure 1 ) [ 5 , 8 , 12 , 14 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ]. All selected studies were published between 2020 and 2022.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These articles were re-evaluated based on full-text contents, resulting in exclusion of 8 articles. Finally, 15 studies met the inclusion criteria and were included in our meta-analysis ( Figure 1 ) [ 5 , 8 , 12 , 14 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ]. All selected studies were published between 2020 and 2022.…”
Section: Resultsmentioning
confidence: 99%
“…Greater clinical value could be found in using KL-6 at admission to predict the subsequent course of COVID-19. Twelve studies involved in our meta-analysis assessed the KL-6 level according to the disease severity [ 6 , 8 , 14 , 19 , 20 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ]. Our analysis demonstrated that there was a significantly higher level of KL-6 in patients suffering from severe COVID-19 than mild-to-moderate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For sensitivity and specificity, data were extracted from eight studies with their baseline values. 9 , 12 , 15 , 17 19 , 21 , 32 The data for sensitivity, and specificity analysis is presented in Supplementary file ( Appendix 4 ). For diagnostic studies, the Summary Receiver Operating Curve (sROC) was performed to summarize TP and FP rates.…”
Section: Methodsmentioning
confidence: 99%
“…Among these Krebs von den Lungen-6 (KL-6) factor has also been established as a possible severity marker and prognostic tool by various articles. 9 21 …”
Section: Introductionmentioning
confidence: 99%